Stimulating Recruitment of Female Managers - Levi, Maurice (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1976)
In order to induce firms to feel indifferent towards the sexes in their recruitment for the administrative level, the cause of preference towards males must be eliminated. In this paper the author discusses the preference for males that arise out of expected lower turnover for male employees.